2009
DOI: 10.1093/jac/dkp108
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey of extended-spectrum β-lactamase-producing Enterobacteriaceae in the French community setting

Abstract: This first nationwide study reports an ESBLE prevalence of 1.1% in the French community setting in 2006, mainly related to the presence of CTX-M-producing E. coli strains; furthermore, unusual co-resistances rarely found in the community setting were occasionally observed, which may threaten future emergence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 47 publications
10
59
0
2
Order By: Relevance
“…The prevalence of 1.3% ESBL-producing E. coli in the community found in this study is similar to that recorded in Spanish and French communities (1.4%) (Arpin et al, 2009;Rodríguez-Baño et al, 2004) but lower than the 5.2% observed in a Spanish multicentre study covering 15 microbiology laboratories in 2006 (Andreu et al, 2008). A study performed in Turkey showed a prevalence of 21% ESBL producers among E. coli causing communityacquired urinary tract infections during (Yumuk et al, 2008.…”
Section: A Barguigua and Others 1348supporting
confidence: 88%
See 3 more Smart Citations
“…The prevalence of 1.3% ESBL-producing E. coli in the community found in this study is similar to that recorded in Spanish and French communities (1.4%) (Arpin et al, 2009;Rodríguez-Baño et al, 2004) but lower than the 5.2% observed in a Spanish multicentre study covering 15 microbiology laboratories in 2006 (Andreu et al, 2008). A study performed in Turkey showed a prevalence of 21% ESBL producers among E. coli causing communityacquired urinary tract infections during (Yumuk et al, 2008.…”
Section: A Barguigua and Others 1348supporting
confidence: 88%
“…The co-existence of different b-lactamases genes within the same isolate, as detected in this study, has also been reported in other countries (Arpin et al, 2009;Woodford et al, 2007). The combination of bla CTX-M-15 +bla OXA-1 +bla TEM-1b was reported in 30 strains from Portugal (Mendonça et al, 2007), and an association between bla SHV-5 and bla TEM-1b has been described in the Brazilian community (Minarini et al, 2007a).…”
Section: A Barguigua and Others 1348supporting
confidence: 85%
See 2 more Smart Citations
“…In a similar study developed in 2006 in the French community setting, the percentage of CTX-M-producing ESBLEC was much higher (83%). SHV-12 was expressed only in 1 of 48 isolates (1). ESBL distribution in Spain is different from that observed in other countries, underlining the great epidemiological variability of these resistance determinants and the need to study them under different epidemiological conditions.…”
Section: Discussionmentioning
confidence: 73%